Comportamento de clones de eucalipto à seca dos ponteiros laterais - Oliveira, Luis Fernando de (2020)
Eucalyptus forests in Brazil are a major driving force in the economy, especially with regard to the paper and cellulose, furniture, wood and energy sectors. However, due to the occupation of the species throughout the national territory, diseases (biotic and abiotic) have become a limiting factor for the eucalyptus production chain, causing great losses. Among the diseases, the drought of lateral pointers (SPL), or drought by Pseudoplagiostoma eucalypti, is, according to specialists, a new disease emerging in national eucalyptus culture. The main strategies for managing the disease are genetic control through the selection of resistant clones, planting in micro-regions unfavorable to the pathogen (escape by location) and unfavorable time of year for the growth of the pathogen (phenological asynchrony). In this sense, this work aims to evaluate the behavior of eucalyptus clones to SPL, in Mucuri, Bahia. The experiment was conducted in an experimental design with 6 randomized blocks, 176 clones and 6 plants per plot, with data collections carried out between the months of June 2017 and March 2018. For the data analysis, the Skott- Knot at 5% probability, with the objective of forming homogeneous groups. The area under the disease progress curve was also calculated to analyze the behavior of the clone in relation to the disease and, finally, a dendrogram diagram was constructed to determine the groups according to the levels of susceptibility. Therefore, it was obtained the formation of three main groups classifying the clones as resistant, moderately resistant, moderately susceptible and susceptible.